Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil - Queiroz, Gabriel C.; de Mendonça, Maria Cleide (Zootaxa, 2010)
Two new Isotomidae species Cryptopygus tingus sp. nov. and Paracerura pindorama sp. nov. are described and illustrated, based on litter samplings made in the year 2008 in the Atlantic Forest of the Sooretama Biological Reserve, in the Espírito Santo State.